Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Siswa di Randusanga Brebes - Bagus Raharjo (LPPM Politeknik Pratama, 2024)
This study aims to describe and analyze the role of Islamic religious education teachers in improving intellectual intelligence, emotional intelligence and spiritual intelligence of students in SD randusanga wetan 2 and SD randusanga kulon 2 Olas, Randusanga wetan District, West Seram Regency. This one. This descriptive qualitative study used observation, interview and documentation data collection methods and involved six researchers, two teachers and four students. Data analysis goes through the following steps: data collection, data reduction, data presentation, data interpretation, and conclusions. The outcome of this study is the role of Islamic religious education teachers in improving students' intellectual intelligence, including planning educational resources, using appropriate methods, teaching and assessment. The role of a teacher of Islamic religious education for emotional inquiry; The Islamic teacher of religious education care for students, student care, student care, takes care of students, teaches students and offers students to students. The role of religious education teachers to improve the spiritual exploration of the students; With all the teachers in the school, the students come to students to students, worship students, because of God's blessings, thank students, worship students, pay attention to students and are polite and polite for students. To pay.